A ficcionalização da vida ribeirinha na contística de Arthur Engrácio - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This work is the result of research that analyze the fictionalization of river life in the tales of Arthur Engrácio and literary devices used by the author to represent amazonian man and contingencies of its existence. The research was guided by the following questions: how it operates the fictionalization of river life in the tales of Arthur Engrácio? What literary devices he uses to represent the amazonian man and the contingencies of its existence? What the theoretical courses are viable for access to him work? The study sought answers to these questions and had the object of study and analysis, the following works of the storyteller: Histórias de submundo (2005), Restinga (1976), Contos do mato (1981), Estórias do rio (1984) e 20 Contos amazônicos (1986). I made the analysis of the work of Engrácio, through the concept of fictionalization of Umberto Eco, Seis passeios pelo bosque da ficção, where fictional work is compared to a forest, choppy trails and choices. This work is presented by different "theoretical ways", including: a semiotic and marvelous realism. The study also contains the analysis of naturalists resonances in work of Engrácio, figures of speech used in the fabric of his stories and the focus of the female figure in the scenario of river life present in the narratives. The methodology of the dissertation route gave up basically by the literature search channel, including this scope: theory texts and literary criticism on literary fictionalization, writings on literature and amazonian culture and the five works of Engrácio, mentioned earlier. The narrative text, like a forest, forces the player to make choices constantly, and through these the reader choices reframes the text. So realize that tales of river life are forests that have multiple paths of access, and in each of them a new expression of the life of the man in the woods, under its various aspects: the fisherman, the rubber, the “juteiro”, the hunter ... Arthur Engrácio builds a fictional forest full of images that express the dynamics of amazon life by the riverside.
Keywords: Vida Ribeirinha; River life; Conto; Arthur Engrácio; LINGUISTICA, LETRAS E ARTES: LETRAS